The impact of pump-power noise on transverse mode instabilities - Stihler, Christoph; Jauregui, Cesar; Tuennermann, Andreas; Limpert, Jens (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
In this work we have investigated the impact of pump-power noise on transverse mode instabilities (TMI) in high-power fiber laser systems. This is a crucial study since former works have shown that pump-power variations can induce a phase shift between the modal interference pattern and the thermally-induced refractive index grating and, thus, they are the most likely trigger for TMI. To experimentally investigate this behavior, we have generated white noise for different frequency bands with an arbitrary waveform generator and applied it to the pump diode. In a first experiment we have evaluated the frequency range of interest. It was found that only frequency components of the pump noise close to the main frequency of the TMI fluctuations influence the TMI threshold of the fiber laser system. In a second experiment we have measured the TMI threshold of the free-running system and compared it to the ones obtained when applying different pump-noise amplitudes. It was found that the TMI threshold can be decreased by almost a factor of three by increasing the noise of the pump source. This result is in good agreement with former theoretical and experimental studies and suggests that pump-power noise indeed acts as a main trigger for TMI. Furthermore, the findings indicate that the development of pump sources and drivers with a low noise level in a frequency range close to the main frequency of the TMI fluctuations could help to increase the TMI threshold of fiber laser systems.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Fiber laser; Mitigation and optimization; Modal interference pattern; Mode instabilities; Phase shift; Pump-power noise; Thermal effects in optical fibers; Thermally-induced refractive index grating